2022
DOI: 10.3390/ijms232113356
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the DNA Damage Response and Immunotherapy Response in Cancer

Abstract: Genome instability and immune evasion are both defining hallmarks of cancer. Tumorigenesis is frequently initiated when there is DNA damage to a proto-oncogene or tumor suppressor gene and DNA repair mechanisms are lost or insufficient to correct the damage; immune evasion then prevents the host immune system from recognizing these transformed cells. Therapies targeting genomic instability and immune evasion have been effectively used to treat cancer. Genotoxic therapies such as chemoradiation have been employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 193 publications
0
3
0
Order By: Relevance
“…Immuno evasion subsequently stops the host immune system from identifying these transformed cells. Cancer has proven to respond well to treatments that target immune evasion and genetic instability ( Lee et al, 2022 ). Variations in DNA damage response genes and the resultant genomic instability have a significant role in determining the antigenicity of tumors via both neoantigen-dependent and independent processes ( Li and Chen, 2018 ).…”
Section: Advancement In Synergy Between Ddr and Itmentioning
confidence: 99%
“…Immuno evasion subsequently stops the host immune system from identifying these transformed cells. Cancer has proven to respond well to treatments that target immune evasion and genetic instability ( Lee et al, 2022 ). Variations in DNA damage response genes and the resultant genomic instability have a significant role in determining the antigenicity of tumors via both neoantigen-dependent and independent processes ( Li and Chen, 2018 ).…”
Section: Advancement In Synergy Between Ddr and Itmentioning
confidence: 99%
“…Immune-mediated mechanisms of tumor development may have some relevance to BRCA1-driven neoplasms, as BRCA1 inactivation is accompanied by the de ciency in homologous DNA repair and, consequently, chromosomal instability. Several studies revealed increased tumor antigenicity for BRCA1-associated hereditary cancers [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It may be mediated by protooncogenes which control various biological processes in normal cells, serving as growth factors, transducers of cellular signals, and nuclear transcription factors [ 6 ]. In mammalian genomes, protooncogenes control normal cell differentiation and proliferation [ 7 ]. Any alterations to these genes that influence the structure of their encoded proteins may result in the development of oncogenes in cancer cells.…”
Section: Introductionmentioning
confidence: 99%